2014
DOI: 10.1007/s00134-014-3391-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the KDIGO acute kidney injury criteria in a pediatric critical care population

Abstract: Using the KDIGO criteria to define AKI, we observed a high prevalence of AKI among critically ill children. Worsening stages of AKI were associated with increased ICU LOS, and AKI was independently associated with prolonged mechanical ventilation and increased mortality. The KDIGO criteria describe clinically relevant AKI in a broad pediatric critical care population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
138
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(152 citation statements)
references
References 25 publications
6
138
2
6
Order By: Relevance
“…Current definitions have demonstrated that even small degrees of AKI are associated with increased morbidity and mortality in children and adults. 1,3,43 This empirical definition has evolved based on observational data from millions of patients and hundreds of studies into the Kidney Diseases: Improving Global Outcomes (KDIGO) AKI definition published in 2013, maintaining a 3-tiered categorical staging model depicting mild, moderate, and severe stages of AKI. 44 The use of standardized definitions of AKI has allowed comparison between studies and was a fundamental first step that has been integral to the study of AKI in medicine.…”
Section: Definition Of Neonatal Akimentioning
confidence: 99%
See 2 more Smart Citations
“…Current definitions have demonstrated that even small degrees of AKI are associated with increased morbidity and mortality in children and adults. 1,3,43 This empirical definition has evolved based on observational data from millions of patients and hundreds of studies into the Kidney Diseases: Improving Global Outcomes (KDIGO) AKI definition published in 2013, maintaining a 3-tiered categorical staging model depicting mild, moderate, and severe stages of AKI. 44 The use of standardized definitions of AKI has allowed comparison between studies and was a fundamental first step that has been integral to the study of AKI in medicine.…”
Section: Definition Of Neonatal Akimentioning
confidence: 99%
“…Some have suggested that the SCr should rise to an absolute value of .0.5 mg/dL and meet the previous criteria to qualify as AKI. 1,12 …”
Section: Definition Of Neonatal Akimentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria provide a standardized simple way of categorizing AKI and may be a better predictor of morbidity and mortality. The RIFLE, AKIN, and KDIGO criteria are summarized in Table 1. KDIGO criteria of AKI were validated in a pediatric critical care population (15). Studies of AKI using KDIGO criteria in orthotopic lung transplant recipients, after cardiac surgery, and in septic patients in critical care units have been published recently, but, to the best of our knowledge, there is no study in the English literature investigating AKI in a cirrhotic population using KDIGO criteria (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Another large cohort study in 580 patients with out-of-hospital cardiac arrest found severe AKI in 43 % of the patients and the association with mortality but not with neurological outcome [3]. Last, it must be noted that first validation of the Kidney Disease Improving Global Outcomes (KDIGO) criteria was performed in a large pediatric population [4]. …”
mentioning
confidence: 99%